A cross-disciplinary primer on the meaning and principles of innovation - Mars, Matthew M.; Hoskinson, Sherry; Libecap, Gary D. (Bingley, U.K. : Emerald, 2013)
Innovation is a central mechanism in the progression of society and often captures the imagination and enthusiasm of corporate leaders, public policy makers, and so on. However, the cultural, political and social complexities of innovation that extend beyond economic and technological contexts are often overlooked. In this volume, a novel approach to deeply understanding innovation in contexts that range from the socio-cultural to the technological is presented. The fundamental principles and constructs of innovation are identified and described according to an interdisciplinary lens that gives particular focus to a variety of historical examples of innovation. This exploration leads to the development of a learning model that serves as an alternative to mainstream innovation curricula.
Introduction / Matthew M. Mars, Sherry Hoskinson -- Framing the conceptual meaning and fundamental principles of innovation / Matthew M. Mars -- Bringing objectivity to the otherwise abstract nature of cultural innovation / Matthew M. Mars -- The forms of innovation : product and process / Matthew M. Mars -- The repurposing and legacy of innovation / Matthew M. Mars -- Assessing the impact of innovation / Matthew M. Mars -- Contemporary conditions and considerations / Matthew M. Mars -- Innovation and entrepreneurship in the context of change / Matthew M. Mars -- Building toward a holistic model of innovation and entrepreneurship education : transformation before commercialization / Matthew M. Mars -- Opportunities and challenges : research and innovation in the life sciences / Randy Burd -- A response and conclusion / Matthew M. Mars.
Print version record
Keywords: Business & Economics -- Entrepreneurship; Business innovation; Finance & accounting; Social entrepreneurship; Social responsibility of business